Bibliometric Analysis of the Concept of Tarbiyah Nabawiyah as the Foundation of Contextual Islamic Education in the Global Era - Nur Fatin Aliyah; Lilih Solih Khatin; M. Misbah (STAI Serdang Lubuk Pakam, 2025)
Social and technological changes in the era of globalization have shifted the orientation of education towards cognitive and technical aspects, thereby marginalizing character building, spirituality, and moral values. This situation has created an urgent need for an educational approach that can maintain the integrity of values while remaining adaptive to the times. Tarbiyah Nabawiyah, as a prophetic education model based on exemplary behavior and the instillation of values, is an important foundation for responding to these challenges. This study maps the development of literature related to Tarbiyah Nabawiyah through a bibliometric analysis of Scopus publications from 2015 to 2025. The data was analyzed using VOSviewer to identify publication trends, author networks, institutional collaborations, and major thematic clusters. The results show a significant increase in studies since 2019 with three dominant clusters: prophetic theological foundations, character-spiritual strengthening, and the integration of prophetic values in modern educational innovation. Publications are dominated by Southeast Asia and the Middle East. These findings provide a structured understanding of the direction of scientific development and have important implications for strengthening Islamic education theory and practice that is more contextual, adaptive, and based on prophetic values.